Pengaruh Tingkat Penghasilan, Pemahaman Aturan Perpajakan, dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM Kabuoaten Buleleng - Handriyani, Putu Ely; Astawa, I Gede Putu Banu (Vokasi : Jurnal Riset Akuntansi, 2022)
This study aims to determine the effect of income level, understanding of taxation rules and socialization of taxation on MSME taxpayer compliance in Buleleng Regency. This research is a quantitative research with the number of respondents as many as 352 MSME taxpayers in Buleleng Regency. Data was obtained by distributing questionnaires directly and through online (google form). The sample was selected using criteria with purposive sampling technique and then calculated using the Slovin formula. The data used is primary data in the form of respondents' answers and processed using the SPSS application. The results of this study indicate that the level of income, understanding of taxation rules and socialization of taxation have a positive and significant impact on MSME taxpayer compliance.